2019
DOI: 10.1186/s40673-019-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

Fever-related ataxia: a case report of CAPOS syndrome

Abstract: Background CAPOS ( C erebellar ataxia, A reflexia, P es cavus, O ptic atrophy and S ensorineural hearing loss) syndrome is caused by the heterozygous mutation, c.2452G > A, in the ATP1A3 gene. Other mutations in this gene can cause a spectrum of overlapping phenotypes including alternating hemiplegia of childhood, rapid onset dystonia par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…3 18 Animal studies have demonstrated that increased temperature leads to more leakage of Na + /K+ ions through the Na + /K + ATPase, providing a possible mechanism for febrile illness triggering CAPOS episodes. 19 Consistent with this mechanism, the patient's spells were easily triggered by overheating either from ambient temperature elevations or from fevers.…”
Section: Discussionmentioning
confidence: 79%
“…3 18 Animal studies have demonstrated that increased temperature leads to more leakage of Na + /K+ ions through the Na + /K + ATPase, providing a possible mechanism for febrile illness triggering CAPOS episodes. 19 Consistent with this mechanism, the patient's spells were easily triggered by overheating either from ambient temperature elevations or from fevers.…”
Section: Discussionmentioning
confidence: 79%
“…AHC, alternating hemiplegia of childhood; ASD, autism spectrum disorder; CAPOS, cerebellar ataxia, areflexia, pes cavus, optic atrophy and sensorineural hearing loss; COS, childhood-onset schizophrenia; CRA, childhood rapid-onset ataxia; D-DEMØ, dystonia, dysmorphism of the face, encephalopathy with developmental delay, brain MRI abnormalities always including cerebellar hypoplasia, no hemiplegia (Ø); NKA, Na + ,K + -ATPase; PMG, polymicrogyria; RDP, rapid-onset dystonia-parkinsonism; RECA, relapsing encephalopathy with cerebellar ataxia. G947R Bourgeois et al, 1993;Heinzen et al, 2012;Ito et al, 2018;Jasien et al, 2019;Panagiotakaki et al, 2010;Rosewich et al, 2012;Schirinzi et al, 2018a;Severino et al, 2020 Demos et al, 2014;Duat Rodriguez et al, 2017;Heimer et al, 2015;Maas et al, 2016;Potic et al, 2015;Rosewich et al, 2014c;Stenshorne et al, 2019 Brashear et al, 2012a;Cook et al, 2014;de Carvalho Aguiar et al, 2004;Dobyns et al, 1993;Haq et al, 2019;…”
Section: Human Nka α 3 Mutationsmentioning
confidence: 99%
“…In CAPOS patients, cochlear outer hair cell activity is preserved, but auditory brainstem responses are grossly abnormal ( Tranebjærg et al, 2018 ). All of the reported cases of CAPOS, to date, are heterozygous for a single recurrent missense mutation, E818K ( Demos et al, 2014 ; Duat Rodriguez et al, 2017 ; Han et al, 2017 ; Heimer et al, 2015 ; Maas et al, 2016 ; Potic et al, 2015 ; Rosewich et al, 2014c ; Stenshorne et al, 2019 ). Some CAPOS patients exhibit mild symptoms, resulting in recovery with minimal residual ataxia ( Demos et al, 2014 ), although one subject with a de novo E818K mutation exhibited only sensorineural hearing loss that began when she was a teenager ( Han et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…CAPOS syndrome, which is derived from the acronym of symptoms like cerebellar ataxia, areflexia, pes cavus, optic atrophy, sensory neural hearing loss, is a very rare disorder; first described in three patients by Nicolaides et al in 1996 1 . Since the original description, about forty patients have been reported and causal association with specific genetic mutation has been established 2 . A missense mutation of the ATP1A3 gene, inherited as autosomal dominant traits with variable expressivity, causes the allelic disorders namely: CAPOS syndrome, rapid -onset dystoniaparkinsonism (RDP) in DYT12 and alternating hemiplegia of childhood (AHC) 3 .…”
Section: Introductionmentioning
confidence: 99%